Bimbingan Teknis (BIMTEK) Aplikasi Dasawisma Bagi Kader Kelurahan Maleer Kecamatan Batununggal Kota Bandung - Suwartika Kusumadiarti, Rini; Aksan Halim, K. Prihartono; Seliwati; Tisnawati, Rini; Kurniawati, Rina; Astriyani Rizky, Ardelia (LPPM Politeknik Piksi Ganesha, 2024)
Technological developments, on the other hand, have the impact of changing human civilization, which is starting to depend on technology. The term IT (Information Technology) which is currently popular is part of a long chain of developments in terms in the world of SI (Information Systems) or IS (Information System). Dasawisma is a group of mothers from 10-20 neighboring households. Dasawisma is part of the PKK cadre who plays a role in improving the quality of life of the community. The management of Dasawisma data in Maleer Village is still done manually, through the handwriting of the heads of Dasawisma per RW, of course this causes difficulties and inefficiencies in reporting data at the RW level. The main objective of this PKM is to create applications, socialization and technical guidance for the Dasawisma Data Filling System in the Maleer Village area, Batununggal District, Bandung City, Socialization of community service programs and implementation of the vision and mission of the Piksi Ganesha Polytechnic Bandung in the surrounding areas, namely Maleer Village, Batununggal District, Bandung City, Establishing cooperation on the tridharma of higher education with the surrounding areas, namely Maleer Village, Batununggal District, Bandung City. It is hoped that the Dasawisma Application designed and initiated by the PKM team of the Piksi Ganesha Polytechnic can help to make data reporting more effective and easier.